Advocates or Challengers of Europeanization? An Inquiry into the Discourse of the Romanian Elites on the European Union in the Context of EU Elections 2014 - Loredana RADU; Alina BÂRGĂOANU (Transylvanian Review of Administrative Sciences, 2015)
This paper aims to shed light on the role of elites in the Europeanization of the national public sphere. 15 semi-structured in-depth interviews with representatives of political, administrative, and media elites in Romania were carried out between March 23 and April 24, 2014, which was on the eve of the 2014 European Elections campaign. Our research shows that, in general, the Romanian elites – be them political, administrative, or media-related – declare themselves as euro-enthusiasts or euro-realists; at the same time, through a diversity of blame-avoiding games, they use the EU as a means of diffusing (national) responsibility for crisis-related hot topics, such as the implementation of austerity measures. By identifying the key narratives of Europeanization in elites’ discourse on the 2014 European Elections, this paper indicates that we witness a paradoxical trend, in which elites are rather challengers than advocates of Europeanization.